Tailorable Brillouin Light Scattering in Air-Slit Suspended Waveguide - Yanzhao Wang; Hongrun Ren; Yunjie Teng (Photonics)
Silicon-based optical waveguides exhibit high Brillouin gain, enabling the realization of Brillouin lasers directly on silicon substrates. These lasers hold significant promise for applications such as tunable-frequency laser emission, ultrafast pulse generation via mode-locking techniques, and other advanced photonic functionalities. However, a key challenge in silicon-based Brillouin lasers is the requirement for long waveguide lengths to achieve sufficient optical feedback and reach the lasing threshold. This study proposes a novel floating waveguide architecture designed to significantly enhance the Brillouin gain in silicon-based systems. Furthermore, we introduce a breakthrough method for achieving wide-range phonon frequency tunability, enabling precise control over stimulated Brillouin scattering (SBS) dynamics. By strategically engineering the waveguide geometry (shape and dimensions), we demonstrate a tunable SBS phonon laser, offering a versatile platform for on-chip applications. Additionally, the proposed waveguide system features adjustable operating frequencies, unlocking new opportunities for compact Brillouin devices and integrated microwave photonic signal sources.